Popular Musical Subcultures: A Contrarian Analysis - Gracyk, Theodore (Scenari, 2024)
Although under attack for reasons articulated by David Hesmondhalgh, the concept of subcultures remains useful for understanding some activities surrounding popular music. However, the concept of subculture must be liberated from problematic assumptions that arose when popular music subcultures were reduced to youth subcultures. Subcultures are cultural formations. As such, they involve persistent symbolic distinction. Understood in this way, some popular music subcultures will be found to align with particular ideologies, but many will be fan formations that are not, for the most part, oppositional to the larger culture.